Efforts To Prevent Stunting In Infants And Toddlers At The Mojosari Health Center, Mojokerto Regency - Dhonna Anggreni; Ika Yuni Susanti Ika; Dyah Siwi Hety Dyah Siwi Hety (JCS, 2023)
Indonesia is currently facing a serious nutritional problem that has an impact on the quality of human resources (HR). One of them is stunting and wasting. Stunting is a chronic malnutrition problem caused by malnutrition over a long period of time, resulting in a child being short (dwarf) for his or her age. As a result of stunting, it not only interferes with physical growth but can also interfere with the development of a child's brain. The purpose of this activity is to increase the knowledge and understanding of mothers of babies and toddlers regarding stunting so that stunting prevention can be done as early as possible. This community service activity was carried out at the Mojosari Mojokerto Health Center. Activities carried out by the method of lectures, question and answer and discussion. From the results of the activity evaluation, it was found that mothers' knowledge and understanding of stunting increased. The hope of this activity is that with this activity, the prevalence of stunting can be reduced, especially in Mojokerto Regency, so that in the future there will be healthy and intelligent children. Keywords: stunting prevention efforts, infants and toddlers